2013
DOI: 10.1152/ajpendo.00105.2013
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for measuring intestinal and hepatic triacylglycerol kinetics

Abstract: Hovorka R, Umpleby AM. A novel method for measuring intestinal and hepatic triacylglycerol kinetics. Am J Physiol Endocrinol Metab 305: E1041-E1047, 2013. First published April 16, 2013; doi:10.1152/ajpendo.00105.2013.-This study aimed to 1) develop a method that completely separated hepatic (VLDL1, VLDL2) and intestinal [chylomicron (CM)] lipoproteins and 2) use the method to measure triacylglycerol (TAG) kinetics in these lipoproteins in the fed and fasting state in healthy subjects, using intravenous [ 2 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…A number of studies have shown that VLDL apoB100 and VLDL TAG production rate is increased by insulin resistance ( 12 , 13 ) in the fasted state, but no studies have measured VLDL TAG production rate quantitatively, in the fed state, in MetS. We have recently demonstrated that intravenously administered 2 H 5 -glycerol is incorporated into CM TAG and can be used to measure both CM and VLDL TAG kinetics in a frequent feeding study ( 14 ). In the current study, we have used this methodology to investigate whether the greater increase in postprandial TAG in MetS compared with lean healthy subjects is due to an increase in CM and/or VLDL TAG production rate or a decrease in clearance rate.…”
mentioning
confidence: 99%
“…A number of studies have shown that VLDL apoB100 and VLDL TAG production rate is increased by insulin resistance ( 12 , 13 ) in the fasted state, but no studies have measured VLDL TAG production rate quantitatively, in the fed state, in MetS. We have recently demonstrated that intravenously administered 2 H 5 -glycerol is incorporated into CM TAG and can be used to measure both CM and VLDL TAG kinetics in a frequent feeding study ( 14 ). In the current study, we have used this methodology to investigate whether the greater increase in postprandial TAG in MetS compared with lean healthy subjects is due to an increase in CM and/or VLDL TAG production rate or a decrease in clearance rate.…”
mentioning
confidence: 99%
“…228 Sun et al developed an immunoaffinity method that completely separated hepatic and intestinal lipoproteins. 229 Using a continuous feeding protocol and an intravenous glycerol tracer in healthy volunteers the authors showed that the FCR of VLDL 1 and VLDL 2 in the fasted state did not differ from the equivalent fraction in a fed state in healthy subjects. The study also measured VLDL and chylomicron TG production rate for the first time in a separate study during a continuous feeding protocol and showed that 47% of total TG production in the Sf > 60 fraction was from chylomicrons.…”
Section: Mechanisms For Prolonged Residence Time Of Trlsmentioning
confidence: 98%
“…Therefore, the separation of the CM-TG component within the S f > 60 fraction (TRL) using immunoaffinity chromatography provides a greater specificity when assessing the enterocyte contribution to circulating TG levels. Sun et al (2013) used this technique to develop a novel stable isotope protocol to enable CM-TG production to be measured in humans in vivo [91]. Shojaee-Moradie et al (2013) [19] utilised the protocol to demonstrate an increased CM-TG concentration in men with metabolic syndrome, compared to lean individuals, which was due to an enhanced CM-TG production rate, with no difference in the CM-TG clearance rate.…”
Section: Fructose Effects On Intestinal Lipoprotein Secretionmentioning
confidence: 99%